Effect of seeding density on suppression of weeds and performance of wheat (Triticum aestivum) - SINGH, TEEKAM (The Indian Journal of Agricultural Sciences, 2014)
An on-farm trial was conducted at five farmer’s field of Banswara district of Rajasthan to validate, refine and popularize the technology developed by Maharana Pratap University of Agriculture and Technology, Udaipur for managing weed flora in wheat (Triticum aestivum L emend. Fiori & Paol) during 2010-11 to 2011-12. Results showed that the seeding density has positive correlation on suppression of weed population. Seeding density over 150 kg/ha significantly suppressed the weed floras. Due to lower weed population and higher yield contributing components under 150 kg/ha seeding density gave 20.8%, 1.4% and 33% more grain yield over 125 and 175 kg/ha and farmer’s practice respectively. The highest net return, B:C ratio, energy output, energy use efficiency, energy productivity and sustainability yield index (SYI) were also recorded with 150 kg/ha seeding density. It can be recommended that 150 kg/ha seeding density of wheat is sufficient to get maximum return in southern Rajasthan and Central Malwa Plateau region. With this intervention tribal farmers of the southern Rajasthan can reduce their cost of production and save energy as well.